Perceived employability among undergraduates and the importance of career self-management, work experience and individual characteristics. Issue 4 (7th June 2017) - Jackson, Denise; Wilton, Nicholas
ABSTRACT: Underemployment, continued growth in the supply of graduates and seemingly perpetual instability are dominant trends in graduate labour markets. In order to negotiate an increasingly complex career terrain, graduates require sharpened skills in effectively managing their own careers and a strong assurance of their own capabilities. This study focuses on the individual dimensions of perceived employability (PE) and explores perceptions among undergraduates and the associated influence of career management competencies, work experience and individual characteristics. Data were collected for 480 business undergraduates at a UK and Australian university using an online survey. Findings indicate that, overall, undergraduates demonstrated reasonably high levels of PE. Certain career management competencies influenced perceptions, in addition to work experience and individual characteristics. The study is relevant to stakeholders, including educators, employers and students, from developed economies as it highlights coherent strategies to enhance PE among higher education students. These may lead to increased individual success in the labour market and more effective recruitment, retention and performance of new graduates.